Faktor-Faktor yang Mempengaruhi Penerimaan PBB P2 di Kota Yogyakarta Pasca Pelimpahan Kewenangan Pengelolaan PBB P2 Oleh Pusat Kepada Daerah - Lastria Nurtanzila; Wahyudi Kumorotomo (Magister Ilmu Administrasi Publik, 2015)
One of the efforts to achieve fiscal independence of local governments is to provide authority in the management of land and property tax as a part of local taxes (Law No.28 of 2009). Yogyakarta has delegated authority to implement this law since 2011. The revenue of PBB P2 pretty much accounted for the PAD, which is why in this study tried to examine the factors that influence Earth Building Tax receipts in the city of Yogyakarta in 2013-2014. So from this study establishes framework there are three factors that can affect PBB P2 in the city of Yogyakarta, which is a factor of tax administration efficiency, effectiveness socialization factor taxation and tax compliance. Based on the research results that the tax administration can efficiently determine the level of awareness of the taxpayer to pay taxes on time, as well as tax sosialization can increase the public's attention on the importance of paying taxes, in addition to the flavor abide by the rules are also important in creating awareness to pay tax.